Temporal variation in end‐member chemistry and its influence on runoff mixing patterns in a forested, Piedmont catchment. Issue 4 (11th April 2013) - Inamdar, Shreeram; Dhillon, Gurbir; Singh, Shatrughan; Dutta, Sudarshan; Levia, Delphis; Scott, Durelle; Mitchell, Myron; Van, John; McHale, Patrick
Key Points Eleven watershed sources and runoff for 42 storm events were studied. End‐member chemistry varied with hydrologic and seasonal conditions. End‐member chemistry and hydrologic connectivity shaped runoff mixing patterns.